Literature Review: Digital Marketing Literacy For SME’s In Pangkalpinang City - Chairunnisa Tri Meidita; Asep Suryana; Kunto Adi Wibowo (Garuda Prestasi Nusantara Consulting, 2025)
This research uses a literature review method, which is employed to identify, evaluate, and interpret existing literature through previously produced works. The aim of this study to identify issues related to digital marketing literacy among MSME’s in Pangkalpinang and to provide research based recommendation regarding digital marketing literacy. The results of the literature review indicate that there are still obstacles in the implementation of digital marketing among MSME’s in Pangkalpinang, primarily due to the lack of knowledge and digital skills possessed by MSME’s. There is a need for more intensive training and guidance related to digital marketing for MSME in Pangkalpinang to support marketing strategies in business activites. Digital marketing literacy plays a crucial role for MSME’s. With good literacy skills, MSME actors can significantly enchance their competitive advantage. Keywords: digital literacy, digital marketing, MSME’s